Foreign policy, domestic politics and international relations the case of Italy - Brighi, Elisabetta (Routledge advances in international relations and global politics, 2013)
This book offers a re-examination of foreign policy, in its relation with domestic politics and international relations (IR). Bringing together a vast body of literature from IR, foreign policy analysis, comparative politics and public policy, this book systematically reconceptualises foreign policy as a dialectic, produced by the interplay of context, strategy and discourse. It argues that foreign policy defies easy understandings and necessitates a complex framework of analysis, introducing the 'Strategic-Relational Model', as conceptualised in critical realism, for the first time to the field of foreign policy analysis. Combining a comprehensive investigation of the last century of Italian foreign policy with an exploration of a key theoretical issue within the field of foreign policy analysis and IR, this book analyses key episodes within Italian foreign policy, including Italy's Cold War alliance politics, colonial interventions, fascist foreign policy and Italy's participation in the wars of Kosovo, Iraq and Afghanistan. It provides a comprehensive and up-to-date account of the long-term historical trajectory of Italian foreign policy, from the Liberal age to the 'Second Republic', including all four governments of Silvio Berlusconi.